Reviewing Criminal Law on Illegal Broadcasting of Paid Football Shows: Mola TV Case Study - Kasim, Muhammad Rinaldy; Karim, M. Said; Judhariksawan, Judhariksawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This study aims to analyse the criminal law regulations regarding the handling of illegal broadcasting actions in paid football shows and to assess the legal status of providers of illegal broadcasting services based on criminal law provisions. The research employs a normative legal method by examining the application of positive legal norms. It consists of normative legal research that utilizes secondary data collection and analysis, as well as empirical legal research that involves obtaining and analysing primary data through interviews with relevant sources. The findings are then analysed qualitatively and systematically organized. The results of the study indicate that (1) the criminal law regulations for addressing illegal broadcasting actions in paid football shows are established in various legislative provisions, including Law No. 28 of 2014 on Copyright, Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Information and Electronic Transactions, and the principles found in Law No. 32 of 2002 on Broadcasting. Despite these regulations, numerous violations still occur. (2) The legal status of organizers of illegal broadcasts who engage in watching/providing/distributing illegal broadcasts violates the applicable regulations. This situation arises because subscription fees charged by Mola TV, the license holder, are still considered expensive, even though the public is generally aware of the relevant legal provisions concerning activities related to watching/providing/distributing illegal broadcasts.